Chemosensitizing Effect of Cernumidine Extracted from Solanum cernuum on Bladder Cancer Cells in Vitro. Issue 10 (12th September 2019) - Miranda, Mariza A.; Mondal, Arindam; Sachdeva, Mandip; Cabral, Hamilton; Neto, Youssef A. A. H.; Khan, Ikhlas; Groppo, Milton; McChesney, James D.; Bastos, Jairo K.
Abstract: Cernumidine (CER) is a guanidinic alkaloid isolated from Solanum cernuum leaves. In this work, we investigated the cytotoxicity, chemosensitizing effect of cernumidine to cisplatin (cDDP) and the possible mechanism of action of the combination on bladder cancer cells. Cernumidine showed cytotoxicity and could sensitize bladder cancer cells to cisplatin. The combination of CER+cDDP inhibited cell migration on T24 cells. CER+cDDP down‐regulated MMP‐2/9 and p‐ERK1/2, while it increased EGFR activity corroborating the observed cell migration inhibition. Down‐regulation of Bcl‐2 and up‐regulation pro‐apoptotic Bax and further depletion of the mitochondrial membrane potential (Δ Ψ m) indicates that mitochondria play a central role in the combination treatment inducing the mitochondrial signaling pathway of apoptosis in T24 cells. Our data showed that the alkaloid cernumidine is worthy of further studies as a chemosensitizing agent to be used in complementary chemotherapy. Abstract :